Water-soluble core mold material as well as preparation method and application thereof
Through the hot pressing technology of collaboratively modified polymer adhesive and quartz sand, the problem of insufficient mechanical properties and stability of water-soluble core mold materials at high temperatures is solved, and higher mechanical properties and water-soluble efficiency are achieved, which is suitable for composite material molding and manufacturing.
Patent Information
- Application Number
- CN202510087451.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The mechanical properties, stability and water-soluble efficiency of existing water-soluble polymer-based core mold materials are difficult to meet the requirements of composite material forming process at higher temperatures, and are prone to aging and cross-linking to lose water-solubleness.
The modified adhesive is formed by using a collaboratively modified polymer adhesive, and a water-soluble polymer with a polymer containing polar functional groups, a polyfunctional polar small molecule and a nanofiller, and is heat-pressed to form a water-soluble core mold material.
The mechanical properties, high-temperature mechanical properties, stability and water-soluble dispersion properties of water-soluble core mold materials are significantly improved, and the needs of composite material molding and manufacturing at higher temperatures are met.
Smart Images

Figure CN119875539A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of advanced composite material molding and manufacturing, and specifically relates to a water-soluble core mold material and a preparation method and application thereof. Background Art
[0002] In the field of modern science and technology physical manufacturing, with the continuous development and progress of molding processing and material technology, parts are increasingly moving towards high performance and lightweight. Composite materials have been widely used in various manufacturing industries due to their excellent performance. At present, a large cost of carbon fiber resin-based composite molding and manufacturing comes from mold manufacturing. For some composite parts with complex geometric features such as hollow special shapes or longitudinal and transverse reinforcements, traditional metal molds have high manufacturing costs and difficult demoulding, which limits the development and progress of composite molding and manufacturing technology. The rubber airbag auxiliary core mold has the problem of poor dimensional accuracy and surface flatness, and cannot meet some high dimensional accuracy manufacturing requirements. The water-soluble core mold can solve the above problems well. It has the advantages of easy molding, economic and environmental protection, high molding accuracy, and easy demoulding. Therefore, it is widely used in various high value-added hollow variable cross-section and complex cavity structure parts manufacturing industries.
[0003] Among the types of water-soluble core molds, compared with salt cores, ceramic cores, gypsum cores and urea cores, polymer-based water-soluble core molds have the advantages of being easier to shape, low cost, environmentally friendly and pollution-free, and strong water-soluble adhesive performance design adjustability, and are widely used in the field of resin-based carbon fiber composite molding. At the same time, in the selection of water-soluble polymer adhesives, the main ones include polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, etc. Because polymers have good molecular structure design, adjustable mechanical properties and water solubility, high toughness and strength, good adhesion, large room for improvement in temperature resistance, low cost, safety and environmental protection, etc., polymer-based water-soluble core molds have good application prospects.
[0004] However, the water-soluble polymer-based core mold materials currently used also face some challenges and difficulties. The main problems are that the mechanical properties, high-temperature mechanical properties and stability are difficult to meet the requirements of the high-temperature composite material curing molding process. The water-soluble efficiency is not high, and high-temperature molding applications are prone to aging and cross-linking and lose water solubility. The current common improvement methods are mainly divided into two categories: chemical modification and blending modification. Among them, blending modification refers to the use of secondary bond forces (hydrogen bonding, Coulomb force, van der Waals force, etc.) to add water-soluble polymers and other modifiers containing polar functional groups to form a mixed system to change the functional group density and aggregation structure of the water-soluble polymer. Common types of blending modification are: (1) blending of water-soluble polymers with polymers containing polar functional groups. By constructing a hydrogen bond network system, the use of polymer macromolecules containing polar functional groups and water-soluble polymers for blending modification can improve the mechanical strength, modulus, glass transition temperature and even adhesion properties of the polymer composite system. (2) Water-soluble polymers are blended with polar small molecules. Multifunctional polar small molecules are added to form hydrogen bonds and other supramolecular forces with water-soluble polymer chains to build a hydrogen bond complex network system, which can improve the strength, toughness and thermal stability of polymer materials. (3) Water-soluble polymers are blended with nanofillers. These nanofillers and polymers are connected through secondary bonds such as hydrogen bonds, and physical energy such as stress, heat energy, and electrical energy are transmitted along the polymer-nanofiller network. The added nanofillers can not only improve the mechanical strength and bonding properties of polymer materials, but also improve thermal stability and antioxidant properties.
[0005] Since the mechanical properties, high-temperature mechanical properties and stability of the water-soluble core mold prepared by a single water-soluble polymer matrix formula are difficult to meet the requirements of the high-temperature composite material curing molding process, and the water-soluble efficiency is not high, it is necessary to develop new modification ideas for the water-soluble core mold to further improve its mechanical properties, high-temperature mechanical properties, stability and water-soluble efficiency. Summary of the invention
[0006] In view of the problems in the prior art, the present invention provides a water-soluble core mold material and a preparation method and use thereof.
[0007] A synergistically modified polymer adhesive is obtained by drying and curing the following raw materials in parts by weight:
[0008] Water-soluble polymer adhesive 0-100 parts,
[0009] 0-100 parts of polymer containing polar functional groups,
[0010] 1 to 9 parts of multifunctional polar small molecules,
[0011] 1 to 12 parts of modified nanofiller;
[0012] The polar functional group is selected from at least one of a carboxyl group and a hydroxyl group;
[0013] The functional groups in the multifunctional polar small molecule are selected from at least one of a hydroxyl group, a carboxyl group and an ester group.
[0014] Preferably, the synergistically modified polymer adhesive is obtained by drying and curing the following raw materials in parts by weight:
[0015] 70 parts of water-soluble polymer adhesive,
[0016] 30 parts of polymer containing polar functional groups,
[0017] 3 parts of multifunctional polar small molecules,
[0018] 4 parts of modified nanofiller.
[0019] Preferably, the water-soluble polymer adhesive is selected from polyvinyl alcohol 、 At least one of polyethylene glycol, polyacrylic acid, polyacrylamide, and polyvinyl pyrrolidone;
[0020] Preferably, the polymer containing polar functional groups is selected from at least one of carboxymethyl cellulose, chitosan, dextran and starch;
[0021] Preferably, the multifunctional polar small molecule is selected from at least one of tannic acid, salicylic acid, citric acid, lactic acid and malic acid;
[0022] Preferably, the modified nanofiller is selected from at least one of polydopamine-coated halloysite nanotubes, polydopamine-coated carbon nanotubes, polydopamine-coated montmorillonite, polydopamine-coated titanium dioxide, and polydopamine-coated silicon dioxide.
[0023] The present invention also provides a method for preparing the above-mentioned synergistically modified polymer adhesive, comprising the following steps:
[0024] Step 1, reacting a water-soluble polymer adhesive solution and an aqueous polymer solution containing polar functional groups to prepare a blended solution 1;
[0025] Step 2, adding nanofiller and polydopamine into water, dispersing by ultrasonication, and drying to obtain modified nanofiller;
[0026] Step 3, after dissolving the multifunctional polar small molecules, adding the modified nanofiller, stirring and dispersing, to prepare a suspension 1;
[0027] Step 4, adding the suspension 1 to the blending solution 1, stirring and then standing to obtain a synergistically modified polymer adhesive.
[0028] Preferably, in step 1, the reaction temperature is 50-70°C;
[0029] And / or, in step 2, the ultrasonic dispersion time is 10-25 min;
[0030] And / or, in step 3, the stirring and dispersing time is 1-2h;
[0031] And / or, in step 4, the stirring temperature is 50-60°C, the stirring time is 1-2h, and the standing time is 24-36h.
[0032] The present invention also provides use of the synergistically modified polymer adhesive in preparing a high temperature resistant water-soluble core mold material.
[0033] A water-soluble core mold material is prepared by mixing the above-mentioned synergistically modified polymer adhesive and quartz sand in a weight ratio of (4-8): (300-500).
[0034] The present invention also provides a method for preparing the water-soluble core mold material, comprising the following steps: mixing the synergistically modified polymer adhesive and quartz sand, and hot-pressing to prepare the water-soluble core mold material.
[0035] Preferably, the hot pressing conditions are to maintain the temperature at 90-110° C. for 0.8-1.5 h, then increase the temperature to 120-135° C. and maintain the temperature at 1.5-2.5 h.
[0036] The present invention also provides the use of the water-soluble core mold material in the field of preparing advanced composite material molding and manufacturing.
[0037] The present invention studies the modification of the water-soluble polymer adhesive component system from three perspectives: polymer blending modification, polar small molecule blending modification, and nanofiller blending modification. The thermal, mechanical and bonding properties of the composite adhesive are synergistically enhanced; the mechanical properties, high-temperature mechanical properties, dimensional stability and water-soluble disintegration properties of the water-soluble core mold material are improved, meeting the requirements of the high-temperature composite material molding manufacturing process.
[0038] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0039] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1Thermogravimetric TGA curve / thermogravimetric rate DTG curve / initial thermal decomposition temperature T i and the maximum thermal weight loss rate temperature T max a) PCMC30@TA composite system; b) PCMC30@HNT composite system; c) PCMC30@TA3@PDA-HNT4 composite system.
[0041] Figure 2 Mechanical properties analysis (tensile strength, Young's modulus and tensile stress-strain curve). a) PCMC30@TA composite system; b) PCMC30@HNT composite system; c) PCMC30@TA3@PDA-HNT4 composite system.
[0042] Figure 3 The bonding performance of adhesives is analyzed by tensile shear strength. a) PCMC30@TA composite system; b) PCMC30@HNT composite system; c) PCMC30@TA3@PDA-HNT4 composite system.
[0043] Figure 4 Comparison of solubility WS% in water at pH = 7. a) PCMC30@TA composite system; b) PCMC30@HNT composite system; c) PCMC30@TA3@PDA-HNT4 composite system.
[0044] Figure 5 Analysis of the 160°C compression performance of PCMC30@TA3@PDA-HNT4 water-soluble core mold material. a) Compression strength; b) Compression modulus; c) Compression stress-strain curve.
[0045] Figure 6 Dimensional stability analysis of PCMC30@TA3@PDA-HNT4 water-soluble core material. a) Static thermomechanical analysis curve in the temperature range of 30-200℃; b) Creep curve at 130℃ and 1.5MPa pressure for 10h.
[0046] Figure 7 Comparison of the 50℃ water-soluble disintegration performance of PCMC30@TA3@PDA-HNT4 water-soluble core mold materials. a) Water flow penetration rate at 50℃; b) Macroscopic morphology of the erosion surface of the core molds with different formula systems after testing; c) Schematic diagram of the mechanism of PDA-coated HNT as a hydrophilic filler to promote the water solubility of the adhesive. DETAILED DESCRIPTION
[0047] In the following examples and experimental examples, reagents and raw materials not specifically described are all commercially available products.
[0048] Example 1 Preparation of PVA / CMC@TA3@PDA-HNT4 composite adhesive and film
[0049] According to the formula in Table 1, firstly, a certain amount of 10wt% PVA (brand: 2488; Macklin reagent) aqueous solution and 4wt% carboxymethyl cellulose (CMC) (MW = 90000 (DS = 0.7), 50-100mPa.s; Aladdin reagent) aqueous solution are stirred and mixed at 60°C according to the solid content mixing ratio of (PVA2488:CMC = 7:3) to obtain a PVA / CMC blended adhesive solution. Halloysite nanotubes (H431905, Aladdin reagent) were coated with dopamine hydrochloride. 1 g of halloysite nanotubes (HNT) and 0.5 g of dopamine hydrochloride were added to 200 mL of deionized water, and ultrasonically dispersed for 15 min. Then, 0.1 mol / L sodium hydroxide solution was added dropwise while stirring to adjust the pH to 8.5. Then, stirring was continued at room temperature for 24 h until the dispersion became dark black. Finally, the dispersion was subjected to multiple centrifugation, washing, drying and grinding to obtain polydopamine-coated HNT (PDA-HNT) powder. Tannic acid TA (98%, Aladdin reagent) (mass fraction of PCMC30 solid content = 3 wt%) was dissolved in 20 ml of deionized water, PDA-HNT powder (mass fraction of PCMC30 solid content = 4 wt%) was added, and the mixture was sealed and stirred for 2 h to obtain a TA-PDA-HNT suspension. Then, a peristaltic pump was used to slowly drip into the PCMC30 blended glue solution, and stirring was continued at 50°C during the dripping. After the dripping was completed, stirring was continued for 2 hours. Finally, ultrasonic treatment was performed and allowed to stand for 24 hours to remove bubbles to obtain a PCMC30@TA3@PDA-HNT4 composite glue solution; the bubble-free PCMC30@TA3@PDA-HNT4 composite solution was cast on a glass plate, naturally dried at room temperature for 24 hours, and then dried again in a vacuum oven at 60°C for 6 hours to remove residual moisture to obtain a PCMC30@TA3@PDA-HNT4 composite film.
[0050] Example 2: Preparation of PVA / CMC@TA3@PDA-HNT4 water-soluble core mold material
[0051] According to the formula in Table 1, the prepared PCMC30@TA3@PDA-HNT4 composite film and 160 mesh quartz sand were mixed at a solid content ratio of 6phr:400phr (equivalent to a mortar ratio of 1.5:10 for 10wt% pure PVA solution and quartz sand), and the PVA / CMC@TA3@PDA-HNT4 water-soluble core mold material was prepared under the hot pressing process conditions of 100℃ / 1h→130℃ / 2h.
[0052] Table 1 Formula composition of PVA / CMC@TA3@PDA-HNT4 water-soluble core mold composite adhesive
[0053]
[0054] The following is the preparation method of the control sample.
[0055] Comparative Example 1: Preparation of PCMC30 Adhesive and Film
[0056] The same preparation method as the PVA / CMC blended adhesive solution (PCMC30) in Example 1 was used to obtain PCMC30 adhesive and film.
[0057] Comparative Example 2: Preparation of PVA / CMC@TA composite adhesive and film
[0058] According to the formula in Table 2, after obtaining the PCMC30 blend solution according to the method of Control Example 1, a certain amount of TA (mass fraction of PCMC30 solid content = 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 9wt%) was dissolved in 20ml of deionized water for use, and then slowly added dropwise to the PCMC30 composite adhesive solution using a peristaltic pump. The subsequent experimental steps were the same as in Example 1 to obtain a PCMC30@TA composite adhesive solution and a film.
[0059] Comparative Example 3: Preparation of PVA / CMC@HNT composite adhesive and film
[0060] According to the formula in Table 2, a PCMC30 blend solution was prepared according to the preparation method in Control Example 1, and then the eidolite nanoclay HNT powder (mass fraction of PCMC30 solid content = 1wt%, 2wt%, 3wt%, 4wt%, 8wt%, 12wt%) was added to 20ml of deionized water, and the mixture was stirred and dispersed for 2h in a sealed state to obtain an HNT suspension. Then, a peristaltic pump was used to slowly dropwise add the mixture into the PCMC30 composite adhesive solution, and the subsequent experimental steps were the same as those in Example 1 to obtain a PCMC30@HNT composite adhesive solution and a film.
[0061] Comparative Example 4: Preparation of PVA / CMC@PDA-HNT4 composite adhesive and film
[0062] HNT was coated with polydopamine. 1g HNT and 0.5g dopamine hydrochloride were added to 200mL deionized water, ultrasonically dispersed for 15min, and then 0.1mol / L sodium hydroxide solution was added dropwise while stirring to adjust the pH to 8.5, and then continued to stir at room temperature for 24h until the dispersion was dark black. Finally, the dispersion was centrifuged, washed, dried and ground several times to obtain polydopamine-coated HNT (PDA-HNT) powder. 4wt% PDA-HNT powder was added to 20ml deionized water, sealed and stirred for 2h to obtain a PDA-HNT suspension. The remaining steps were the same as those in Control Example 3 to obtain a PCMC30@PDA-HNT4 composite adhesive solution and film.
[0063] Comparative Example 5: Preparation of PVA / CMC@TA3@HNT4 composite adhesive and film
[0064] According to the formula in Table 2, the PCMC30 blend solution was prepared according to the preparation method in Control Example 1, and then 0.309g of TA (accounting for the PCMC30 solid content mass fraction = 3wt%) was dissolved in 20ml of deionized water, and 0.417g of HNT powder (accounting for the PCMC30 solid content mass fraction = 4wt%) was added, and the mixture was sealed and stirred for 2h to obtain a TA-HNT suspension. Then, a peristaltic pump was used to slowly dropwise add the mixture into the PCMC30 blended adhesive solution, and the subsequent experimental steps were the same as in Example 1 to obtain a PCMC30@TA3@HNT4 composite adhesive solution and film.
[0065] Table 2. Composition of the control sample
[0066]
[0067]
[0068] The beneficial effects of the present invention are demonstrated by experimental examples below.
[0069] Experimental Example 1: Thermal Performance Analysis of PVA / CMC@TA / HNT
[0070] The @TA3@PDA-HNT4-Mold, PCMC30-Mold,
[0071] @TA1-Mold, @TA2-Mold, @TA3-Mold, @HNT1-Mold, @HNT2-Mold, @HNT4-Mold, @HNT8-Mold, @HNT12-Mold, @PDA-HNT4-Mold,
[0072] @TA3@HNT4-Mold samples were prepared according to the methods of the examples or control examples.
[0073] 1. Experimental Methods
[0074] Thermogravimetric analysis of PVA and PVA composite films was performed using TG209F1 thermogravimetric analyzer to characterize their thermal stability. The temperature was raised from 30°C to 800°C at a heating rate of 10°C / min in a N2 atmosphere, and the thermogravimetric curves were recorded.
[0075] The glass transition temperature (T) of the film samples was measured by Q800 dynamic mechanical analyzer in tension mode. g The test characterization was carried out. The test frequency was selected as 1 Hz, the amplitude was 15 μm, the heating rate was 3 ° C / min, and the temperature scanning test was carried out in the range of 20 ° C to 170 ° C.
[0076] 2. Experimental Results
[0077] like Figure 1 As shown in a, with the increase of TA content, the PCMC30@TA composite system T i and T max All of them have increased to varying degrees. i From 276.3℃(PCMC30) to 284.2℃(PCMC30@TA3), an increase of 7.9℃; T max The temperature increased from 303.6℃ (PCMC30) to 308.2℃ (PCMC30@TA3), an increase of 4.6℃. The dehydration weight loss rate (the mass loss rate corresponding to the first peak around 120℃ on the DTG curve) decreased to 8.63%.
[0078] Secondly, from Figure 1 As can be seen in b, with the increase of HNT content, the dehydration weight loss rate continues to decrease, and the T i and T max The values first increase and then decrease, with the maximum value appearing when the HNT content is 4 wt% (T i =287.8℃, T max =321.1℃, dehydration weight loss rate = 7.26%). Its thermal stability is better than PCMC30 (T i =276.3℃, T max =303.6℃, dehydration weight loss rate = 9.60%) has been greatly improved, T i and T max They increased by 11.5℃ and 17.5℃ respectively.
[0079] Next, 3wt% TA, 4wt% HNT and 4w% PDA-HNT were added into the PCMC30 system to study their synergistic effect on the thermal stability of the PCMC30 matrix. Figure 1 As shown in c, compared with PCMC30@TA and PCMC30@HNT composite systems, PCMC30@TA3@HNT4 has a higher T i The temperature was increased to 289.1℃, and the dehydration weight loss rate was further reduced to 6.02%, indicating that the addition of 3wt% TA and 4wt% HNT to the PCMC30 system has a synergistic enhancement effect on its thermal stability. In addition, after 3wt% TA and 4wt% PDA-HNT were added to the PCMC30 system, its thermal degradation curve and initial thermal decomposition temperature were almost the same as those of the PCMC30@TA3@HNT4 complex, indicating that PDA (the thermal decomposition temperature of PDA is around 180℃) coating HNT does not affect its synergistic enhancement effect with TA on the thermal stability of the PCMC30 system.
[0080] The experimental results show that the addition of TA and HNT respectively can improve the thermal stability of the PCMC30 system to a certain extent, and the addition of 3wt% TA and 4wt% PDA-HNT to the PCMC30 system has a synergistic enhancement effect on its thermal stability.
[0081] Experimental Example 2: Mechanical Properties Analysis of PVA / CMC@TA / HNT
[0082] The @TA3@PDA-HNT4-Mold, PCMC30-Mold,
[0083] @TA1-Mold, @TA2-Mold, @TA3-Mold, @TA4-Mold, @TA5-Mold,
[0084] @HNT1-Mold, @HNT2-Mold, @HNT4-Mold, @HNT8-Mold, @HNT12-Mold, and @TA3@HNT4-Mold samples were all prepared according to the methods of the embodiments or control examples.
[0085] 1. Experimental Methods
[0086] The film samples were tested for mechanical properties using a tensile performance test using an Instron 5966 universal testing machine (tensile mode). Dumbbell-shaped standard samples (total length 115 mm, narrow neck width 6 mm) were made according to GB / T1040-2006, with a tensile speed of 50 mm / min. Each group of samples was tested 5 times and the average value was taken.
[0087] 2. Experimental Results
[0088] First, we compared the typical tensile properties of PCMC30@TA composite films that can be cast into films with 0-5wt% TA addition, such as tensile strength, Young's modulus and elongation at break. Figure 2 As shown in Figure a, with the addition of TA, the tensile strength and modulus of the PCMC30@TA composite film first increase and then decrease, reaching the maximum value of 137MPa and 7.7GPa at 3wt% TA addition, which are 26% and 13% higher than PCMC30, respectively. The elongation at break also increases first and then decreases.
[0089] from Figure 2b It can be seen that with the increase of HNT content (0-12wt%), the mechanical strength and Young's modulus of PCMC30@HNT composite film first increased and then decreased, reaching the maximum value of 145MPa and 8.6MPa at 4wt% HNT addition, which increased by 33% and 27% respectively. The elongation at break only showed a downward trend. The results show that the appropriate loading amount of HNT has a good effect on improving the mechanical properties of the PCMC30 system.
[0090] like Figure 2 As shown in Figure c, when 3wt% TA and 4wt% HNT are added to the PCMC30 system, the tensile strength and elongation at break are further increased relative to the PCMC30@TA3 composite film and PCMC30@HNT4 composite film, and the tensile strength and elongation at break are increased to 147MPa and 4.15%, respectively, indicating that TA and HNT have a synergistic effect in the PCMC30 system. Compared with PCMC@TA3@HNT4, PCMC30@TA3@PDA-HNT4 has a small increase in tensile strength (increase of 2MPa) and modulus (increase of 0.4GPa).
[0091] The experimental results show that 3wt% TA and 4wt% HNT can improve the mechanical strength and modulus of the PCMC30 system. When both are added to the PCMC30 system, the tensile strength and elongation at break are further increased, indicating that TA and HNT produce a synergistic effect in the PCMC30 system, and the synergistic effect between PDA-HNT and TA is stronger.
[0092] Experimental Example 3: Analysis of the bonding performance of PVA / CMC@TA / HNT
[0093] The @TA3@PDA-HNT4-Mold, PCMC30-Mold,
[0094] The @TA1-Mold, @TA2-Mold, @TA3-Mold, @TA4-Mold, @HNT0.5-Mold, @HNT1-Mold, @HNT2-Mold, @HNT4-Mold, and @TA3@HNT4-Mold samples were all prepared according to the methods of the embodiments or control examples.
[0095] 1. Experimental Methods
[0096] The bonding performance test was carried out by using an Instron 5966 universal testing machine to perform lap tensile shear tests on the adhesive samples. According to ISO 4587:2003 standard, a quartz sheet was used as the lap sheet, and the room temperature bonding strength of the samples was tested at a test rate of 5 mm / min. Each group of samples was tested 5 times and the average value was taken.
[0097] 2. Experimental Results
[0098] like Figure 3 As shown in Figure a, with the increase of TA content, the tensile shear strength of PCMC30@TA composite adhesive first increases and then decreases, reaching a maximum value of 1.47MPa at 3wt% TA addition (an increase of 63% relative to PCMC30), that is, PCMC30@TA3 has the best bonding strength.
[0099] from Figure 3 b It can be seen that with the increase of HNT content, the tensile shear strength of PCMC30@HNT has almost no change compared with the PCMC30 matrix, which is around 0.9 MPa, indicating that the addition of HNT has little effect on the bonding strength of the PCMC30 system.
[0100] Depend on Figure 3 c It can be seen that when 3wt% TA and 4wt% HNT are added to the PCMC30 adhesive system, its bonding strength is still lower than that of the PCMC30@TA3 composite adhesive, and the expected synergistic enhancement effect is not achieved. After the HNT is coated with polydopamine, the bonding strength of the PCMC30@TA3@PDA-HNT4 composite adhesive is increased to 1.70MPa, which is 95% and 16% higher than that of PCMC30 and PCMC30@TA3, respectively. This shows that only when TA is added to the PCMC30 system together with PDA-HNT can its bonding performance be synergistically enhanced.
[0101] The experimental results show that the addition of TA increases the bonding strength of the PCMC30 system, and the addition of HNT has little effect on the bonding strength of the PCMC30 system. However, the synergistic addition of 3wt% TA and 4wt% PDA-HNT to the PCMC30 adhesive system has a synergistic effect on its bonding performance.
[0102] Experimental Example 4: Analysis of the dissolution performance of PVA / CMC@TA / HNT
[0103] The @TA3@PDA-HNT4-Mold, PCMC30-Mold,
[0104] @TA1-Mold, @TA2-Mold, @TA3-Mold, @HNT1-Mold, @HNT2-Mold, @HNT4-Mold, @HNT8-Mold, @HNT12-Mold, @PDA-HNT4-Mold,
[0105] @TA3@HNT4-Mold samples were prepared according to the methods of the examples or control examples.
[0106] 1. Experimental Methods
[0107] The solubility of the film sample in a water environment with a pH of 7 was tested by dry matter weighing method. The prepared film sample was cut into 20×20 mm 2 , and store in a desiccator. The dry mass before dissolution is recorded as the initial mass m i Then, all samples were placed in a beaker filled with 80 mL of deionized water and soaked at room temperature for 1 hour. Subsequently, the insoluble residue was filtered and dried at 60 °C to a constant weight, which was the dry mass m remaining after dissolution. f The water solubility of the sample at pH = 7 is calculated by the following formula: Solubility (WS%) = m i -m f / m i × 100%. Each sample was measured 5 times and the average value was calculated to obtain the final result.
[0108] 2. Experimental Results
[0109] Depend on Figure 4 It can be seen from Fig. 5 that the addition of tannic acid (TA) (no more than 3 wt%) reduces the solubility of the PCMC30 system to a certain extent, from 45.5% of PCMC30 to 37.0% of PCMC30@TA3.
[0110] However, from Figure 4 As can be seen in b, with the increase of HNT content, the solubility WS% of the PCMC30@HNT composite system first increases and then decreases, with the maximum value being 53.0% (4wt% content).
[0111] like Figure 4 As shown in Figure c, the solubility WS% of PCMC30@TA3@HNT4 is 37.6%, which is between PCMC30@TA3 and PCMC@HNT4. It is the result of the combined effect of TA inhibiting dissolution and HNT promoting dissolution. After HNT is modified by PDA coating and then added to the PCMC30 system together with 3wt% TA, the WS% of PCMC30@TA3@PDA-HNT4 is further increased to 40.3%.
[0112] The experimental results show that the addition of TA (no more than 3wt%) reduces the solubility of the PCMC30 system, and the addition of HNT promotes the dissolution of PCMC30 to a certain extent. After the addition of both, the solubility of PCMC30@TA3@HNT4 is between PCMC30@TA3 and PCMC@HNT4, while the solubility of PCMC30@TA3@PDA-HNT4 is further increased, and the water solubility performance is improved.
[0113] Experimental Example 5: Mechanical Properties Analysis of PVA / CMC@TA / HNT Core Material
[0114] The @TA3@PDA-HNT4-Mold, PCMC30-Mold,
[0115] @TA3-Mold and @PDA-HNT4-Mold water-soluble core mold materials were prepared according to the methods of the embodiments or control examples.
[0116] 1. Experimental Methods
[0117] The UTM5105S composite material high temperature mechanical loading system (compression fixture) was used to test the compression performance of the water-soluble core sample at a certain temperature. In reference to the GB / T 17671-1999 standard, the compression rate was 2400±200N / s and the maximum load of the sensor was 100kN. The average value was taken after five tests.
[0118] 2. Experimental Results
[0119] like Figure 5 As shown in the figure, compared with the PCMC30 core mold, the addition of 3% TA increased the compressive strength by 32% and decreased the compressive modulus by 17%; the addition of 4PDA@HNT had almost no effect on the compressive strength and modulus; and the addition of 3% TA and 4% PDA@HNT to PCMC30 increased the strong compressive strength by 22% and the compressive modulus by 5%. The experimental results show that the high temperature compressive strength of the PVA / CMC@TA3@PDA-HNT4 core mold material is improved, the bonding strength is improved, and the ability to resist thermal deformation is enhanced.
[0120] Experimental Example 6: Dimensional stability analysis of PVA / CMC@TA / HNT core mold material
[0121] The @TA3@PDA-HNT4-Mold, PCMC30-Mold,
[0122] @TA3-Mold and @PDA-HNT4-Mold water-soluble core mold materials were prepared according to the methods of the embodiments or control examples.
[0123] 1. Experimental Methods
[0124] High temperature long-term compression creep test, using UTM5105S composite material high temperature mechanical loading system (compression fixture) to carry out high temperature long-term compression creep test on water-soluble core mold blocks to characterize their high temperature dimensional stability. The core mold blocks are placed in a 130°C environmental test box, under a pressure of 1.5MPa, and the force is maintained for 10 hours to obtain the strain-time curve of the core mold sample and calculate the final creep amount.
[0125] Static thermomechanical analysis (TMA) was performed using a Q400 static thermomechanical analyzer in compression mode to characterize the thermal expansion coefficient of the core sample. The test standard sample size was 5mm×5mm×4mm, the preload force was (4.0±0.1)KPa, and the temperature was increased from room temperature to 200℃ at a heating rate of 5℃ / min in a N2 atmosphere.
[0126] 2. Experimental Results
[0127] from Figure 6 It can be seen that the linear expansion coefficients of PCMC30@TA3 and PCMC30@PDA-HNT4 core molds are 10.27×10 -6 / K and 10.49×10 -6 / K, compared with PCMC30 blending core mode reduced by 2.44×10 -6 / K and 2.22×10 -6 / K; Secondly, the linear expansion coefficient of the core mold material prepared by adding 3wt% TA and 4wt% PDA-HNT into PCMC30 was further reduced to 9.67×10 -6 / K.
[0128] In addition, the 130℃ compression creep test on the PCMC30@TA3@PDA-HNT4 core mold material showed that the compression creep curves of the core molds prepared by these three formulas were similar to those of the PCMC30 blend core mold, and all showed four stages: transition creep stage, compression strain reduction stage, creep equilibrium stage, and creep constant rate stage. Figure 6 b It can be seen that the expansion of PCMC30@TA3, PCMC30@PDA-HNT4 and PCMC30@TA3@PDA-HNT4 core mold materials in the second stage is smaller than that of PCMC30 blend core mold, with the minimum being only 1.21% (PCMC30@TA3@PDA-HNT4), which is consistent with Figure 6 From the creep amount of the whole stage, the compression dimensional change rate of the PCMC30@TA3@PDA-HNT4 core mold material is the lowest.
[0129] The experimental results show that adding 3wt% TA and 4wt% PDA-HNT separately to the PCMC30 adhesive system can improve the dimensional stability of the core mold material under thermal expansion and its ability to resist thermal deformation; when both are added together, a synergistic effect is produced in the PCMC30 system, which improves the ability of the core mold to resist thermal deformation and improves the dimensional stability of the core mold material.
[0130] Experimental Example 7: Analysis of water solubility and disintegration of PVA / CMC@TA / HNT core mold material
[0131] The @TA3@PDA-HNT4-Mold, PCMC30-Mold,
[0132] @TA3-Mold and @PDA-HNT4-Mold water-soluble core mold materials were prepared according to the methods of the embodiments or control examples.
[0133] 1. Experimental Methods
[0134] The water flow scouring test device and method of patent CN116223311A are used to test the water-soluble disintegration performance of the core mold sample.
[0135] 2. Experimental Results
[0136] Depend on Figure 7 It can be seen from a that compared with the PCMC30 blended core mold, the water flow penetration rate of the PCMC30@TA3 core mold material dropped to 0.31 mm / s, a decrease of 74%; the water flow penetration rate of the PCMC30@PDA-HNT4 core mold material increased to 1.36 mm / s, an increase of 14%;
[0137] The water flow penetration rate of PCMC30@TA3@PDA-HNT4 core material still dropped to 0.42mm / s, a decrease of 65%. Figure 7 From the perspective of the erosion surface collapse area of the core molds prepared by the four formulas in b, the PCMC30@PDA-HNT4 core mold material has the largest area, followed by the PCMC30 blended core mold material, while the water-soluble collapse area of the PCMC30@TA3 core mold material and the PCMC30@PDA-HNT4 core mold material is relatively small. Figure 7 As shown in c, the polydopamine PDA coating further improves the hydrophilicity of PDA@HNT and increases the water dissolution rate due to its high dispersibility and high hydrophilicity in aqueous solution.
[0138] The experimental results show that the addition of TA significantly reduces the water-soluble disintegration properties of PCMC30 core mold material. On the contrary, the addition of PDA-HNT can improve its water-soluble disintegration properties.
[0139] The water-soluble disintegration performance of the PCMC30@TA3@PDA-HNT4 core mold material is the result of the combined effect of the inhibitory effect of TA and the promoting effect of PDA-HNT, but from the perspective of the degree of reduction in the water flow penetration rate, the inhibitory effect of TA is more obvious.
[0140] In summary, the present invention starts from the three perspectives of polymer blending modification, polar small molecule blending modification and nanofiller blending modification, and selects carboxymethyl cellulose (CMC), tannic acid (TA) and polydopamine-coated pyroxene nanotubes (PDA-HNT) to modify the water-soluble PVA adhesive component system. The results show that the thermal, mechanical and bonding properties of the PCMC30@TA3@PDA-HNT4 composite adhesive are enhanced, and the water solubility is improved; the mechanical properties, high-temperature mechanical properties and water solubility of the PCMC30@TA3@PDA-HNT4 water-soluble core mold material are better in terms of mechanical properties, high-temperature mechanical properties and water solubility, the compression strength is improved, the dimensional stability is also improved, and the degree of reduction in water-soluble dissipation rate is small, which can be used to solve the problem that the mechanical properties, high-temperature mechanical properties and stability of the water-soluble core mold prepared with a single PVA matrix formula are difficult to meet the requirements of the high-temperature composite material curing molding process.
Claims
1. A synergistically modified polymer adhesive, characterized in that: It is obtained by drying and solidifying the following raw materials in parts by weight: Water-soluble polymer adhesive 0-100 parts, 0-100 parts of polymer containing polar functional groups, 1 to 9 parts of multifunctional polar small molecules, 1 to 12 parts of modified nanofiller; The polar functional group is selected from at least one of a carboxyl group and a hydroxyl group; The functional groups in the multifunctional polar small molecule are selected from at least one of a hydroxyl group, a carboxyl group and an ester group.
2. The synergistically modified polymer adhesive according to claim 1, characterized in that: It is obtained by drying and solidifying the following raw materials in parts by weight: 70 parts of water-soluble polymer adhesive, 30 parts of polymer containing polar functional groups, 3 parts of multifunctional polar small molecules, 4 parts of modified nanofiller.
3. The synergistically modified polymer adhesive according to claim 1 or 2, characterized in that: The water-soluble polymer adhesive is selected from polyvinyl alcohol 、 At least one of polyethylene glycol, polyacrylic acid, polyacrylamide and polyvinyl pyrrolidone.
4. The synergistically modified polymer adhesive according to claim 1 or 2, characterized in that: The polymer containing polar functional groups is selected from at least one of carboxymethyl cellulose, chitosan, dextran and starch; And / or, the multifunctional polar small molecule is selected from at least one of tannic acid, salicylic acid, citric acid, lactic acid and malic acid.
5. The synergistically modified polymer adhesive according to claim 1 or 2, characterized in that: The modified nanofiller is selected from at least one of polydopamine-coated halloysite nanotubes, polydopamine-coated carbon nanotubes, polydopamine-coated montmorillonite, polydopamine-coated titanium dioxide, and polydopamine-coated silicon dioxide.
6. The method for preparing the synergistically modified polymer adhesive according to any one of claims 1 to 5, characterized in that: The steps include: Step 1, reacting a water-soluble polymer adhesive solution and an aqueous polymer solution containing polar functional groups to prepare a blended solution 1; Step 2, adding nanofiller and polydopamine into water, dispersing by ultrasonication, and drying to obtain modified nanofiller; Step 3, after dissolving the multifunctional polar small molecules, adding the modified nanofiller, stirring and dispersing, to prepare a suspension 1; Step 4, adding the suspension 1 to the blending solution 1, stirring and then standing to obtain a synergistically modified polymer adhesive.
7. Use of the synergistically modified polymer adhesive according to any one of claims 1 to 5 in the preparation of high temperature resistant water-soluble core mold materials.
8. A water-soluble core mold material, characterized in that: The invention is prepared by mixing the synergistically modified polymer adhesive described in any one of claims 1 to 5 and quartz sand in a weight ratio of (4-8): (300-500).
9. The method for preparing the water-soluble core mold material according to claim 8, characterized in that: The method comprises the following steps: mixing the synergistically modified polymer adhesive and quartz sand, and hot pressing to prepare a water-soluble core mold material.
10. Use of the water-soluble core mold material according to claim 8 in the field of preparing advanced composite material molding and manufacturing.
Citation Information
Patent Citations
Method and device for testing water-soluble collapsibility of water-soluble core mold material
CN116223311A
Adhesive composition, adhesive comprising same, and manufacturing method therefor
CN111094492A
Dopamine modified halloysite nanotube / polyamide forward osmosis membrane and preparation and application thereof
CN114984765A
High-strength heat-resistant polyvinyl alcohol composite film based on modified halloysite nanotube crosslinking and preparation method thereof
CN118406331A
Preparation method of hierarchical porous PVA aerogel with flame-retardant and heat-insulating properties
CN118930950A
Cited By
Metal-plastic bonding aid and bonding method thereof
CN120904813A